2019
DOI: 10.1080/0361073x.2019.1664450
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Changes in Real-time Conscious Postural Processing by Older Adults during Different Stance Positions Using Electroencephalography Coherence

Abstract: Investigating changes in real-time conscious postural processing by older adults during different stance positions using electroencephalography coherence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Balance performance declines with age due to biological changes (e.g. mobility, physical inactivity), which in turn could lead to falls [ 16 , 17 ]. LBP is known to be an independent risk factor for recurrent falls in older women [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Balance performance declines with age due to biological changes (e.g. mobility, physical inactivity), which in turn could lead to falls [ 16 , 17 ]. LBP is known to be an independent risk factor for recurrent falls in older women [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, considering psychological factors closely related to movement execution seems a promising approach: Studying people’s thoughts or expectations regarding their own movements might not only explain error-prone movement behavior but could also be a way to explore the underlying mechanism of this specific motor-function failure. As falls often happen during highly automatized movements such as walking or running, it might be that movement failure is due to cognitive control while moving [ 20 , 22 , 24 , 25 ]. Instead of performing an automatized movement, people seem to consciously control movement execution, which results in performance decrements.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, so far, older people’s movement-specific reinvestment tendency has received only limited attention [ 21 , 22 , 23 , 25 , 26 , 34 , 35 , 36 ]. Previous research demonstrated the association between movement-specific reinvestment and cognitive processing, in measures of planning, brain activity, and gaze behavior [ 25 , 26 , 35 , 37 ]. Beyond cognition, conscious movement control has also been shown to increase with task difficulty during gait [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Motor performance declines with age due to biological changes (e.g. mobility, physical inactivity), which in turn can lead to falls [16,17] . LBP is a known independent risk factor for repeated falls in older women [18] .…”
Section: Introductionmentioning
confidence: 99%